Secure multi-authority attribute-based encryption with cache-aware scheduling for mobile cloud access control - Jamal, Fara; Abdullah, Mohd Taufik; Mohd Hanapi, Zurina; Abdullah, Azizol (IAEME Publication, 2020)
Outsourcing confidential data to an untrusted cloud system and allowing mobile device access have raised numerous security issues and delay in access. The main concern is the availability of the required data and the integrity in the decision to allow access to the data. The first line of defence that prevents unauthorized access to the data is known as access control. Fine-grained access control using attribute-based encryption mechanisms can be enforced as the first line of defence on the untrusted cloud to forbid unauthorized access to the stored data. In ABE, the key issuing authority will decide whether to allow or refuse user access. However, the current technique has a minor failure in authority and depends on centralizing storage. Security attacks on the current method prove that the existing scheme encounters security flaws. The authority and storage can be the cause of failure that will tarnish the ABE availability. At the same time, the integrity of the key authority can be questioned due to key abuse. To overcome this challenge, a novel multi-authority with failover node and decentralized storage with consensus authority mechanism was introduced to increase the scheme's availability and integrity. Furthermore, communication complexity is increasing between mobile devices and the cloud, especially during peak hours. To improve these issues, the cache-aware scheduling technique was used to reduce the time and read in a cloud environment.